1998
DOI: 10.1021/bi9817055
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Interactions within a Ternary Complex of the Bacteriophage T4 Recombination Proteins uvsY and gp32 Bound to Single-Stranded DNA

Abstract: The presynaptic phase of homologous recombination requires the formation of a filament of single-stranded DNA (ssDNA) coated with a recombinase enzyme. In bacteriophage T4, at least three proteins are required for the assembly of this presynaptic filament. In addition to the T4 recombinase, uvsX protein, the T4 ssDNA binding protein (gp32), and the uvsY recombination accessory protein are also required. Here we report on a detailed analysis of a tripartite filament containing ssDNA bound by stoichiometric quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 40 publications
8
57
0
Order By: Relevance
“…Finally, a third possibility relies on proteinprotein interactions that exist between Rad52 protein and RPA and between Rad52 and Rad51 protein; in principle, these three proteins could form a transient Rad51-Rad52-RPAssDNA nucleoprotein co-complex as an intermediate. In the T4 phage system, a three-protein and DNA co-complex was proposed as an intermediate (30), but recent studies have shown that the gp32-ssDNA interaction is destabilized by interaction with UvsY protein to facilitate loading of UvsX protein onto ssDNA (37). So far, however, we have not detected any destabilization of the RPA-ssDNA complex by Rad52 protein.…”
Section: Displacement Of Rpa From Ssdna Is Limited By Nucleation Of Amentioning
confidence: 60%
“…Finally, a third possibility relies on proteinprotein interactions that exist between Rad52 protein and RPA and between Rad52 and Rad51 protein; in principle, these three proteins could form a transient Rad51-Rad52-RPAssDNA nucleoprotein co-complex as an intermediate. In the T4 phage system, a three-protein and DNA co-complex was proposed as an intermediate (30), but recent studies have shown that the gp32-ssDNA interaction is destabilized by interaction with UvsY protein to facilitate loading of UvsX protein onto ssDNA (37). So far, however, we have not detected any destabilization of the RPA-ssDNA complex by Rad52 protein.…”
Section: Displacement Of Rpa From Ssdna Is Limited By Nucleation Of Amentioning
confidence: 60%
“…In the T4 RDR in vitro system, uvsY dramatically lowers the critical concentration of uvsX protein required for initiating the leading strand synthesis component (5). UvsY carries out two important functions that enable it to stimulate uvsX-catalyzed recombination events (9,12): (i) uvsY helps uvsX displace gp32 from ssDNA, a reaction necessary for proper formation of the presynaptic filament; and (ii) uvsY interacts with and stabilizes uvsX-ssDNA filaments after they are assembled.…”
Section: Role Of Uvsy Protein In Assembly Of the T4 Presynaptic Filamentmentioning
confidence: 99%
“…These are DNA-binding proteins that show strong affinity for cognate SSB-ssDNA (Umezu and Kolodner 1994;Sweezy and Morrical 1999;Beernink and Morrical 1998;Sugiyama and Kowalczykowski 2002), and that lack any sequence homology with the RecA family. They possess intrinsic annealing activities (discussed below) that play separate and distinct roles in recombination from RMP activity (Kantake et al 2002).…”
Section: Annealing Proteins With Rmp Activitymentioning
confidence: 99%
“…The mechanism of Rad52-promoted annealing of RPA-ssDNA complexes involves the formation of a ternary Rad52-RPA-ssDNA complex (Shinohara et al 1998;Sugiyama et al 1998). This mechanism appears to be conserved as both RecO and UvsY show similar interactions with cognate SSB-ssDNA complexes (Sweezy and Morrical 1999;Ryzhikov et al 2011;Ryzhikov and Korolev 2012). The annealing activity of S. cerevisiae Rad52 protein is stimulated by Rad59, a paralog of Rad52 (Davis and Symington 2001;Wu et al 2006).…”
Section: Dna-annealing Proteins In Hrmentioning
confidence: 99%